2015
DOI: 10.1111/tpj.12779
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium T‐DNA integration into the plant genome can occur without the activity of key non‐homologous end‐joining proteins

Abstract: SUMMARYNon-homologous end joining (NHEJ) is the major model proposed for Agrobacterium T-DNA integration into the plant genome. In animal cells, several proteins, including KU70, KU80, ARTEMIS, DNA-PKcs, DNA ligase IV (LIG4), Ataxia telangiectasia mutated (ATM), and ATM-and Rad3-related (ATR), play an important role in 'classical' (c)NHEJ. Other proteins, including histone H1 (HON1), XRCC1, and PARP1, participate in a 'backup' (b)NHEJ process. We examined transient and stable transformation frequencies of Arab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 70 publications
1
41
0
Order By: Relevance
“…In addition, heterogeneous T‐DNA integration caused a cascade of new junctions. Several reports have shown that Agrobacterium transformation would delay the closure of DSB (Vaghchhipawala et al ., ; Park et al ., ). We hypothesize that Agrobacterium could hijack the DSB repair mechanism of target cells and provide the opportunity to heterogeneous T‐DNA integration and occurrence of new junctions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, heterogeneous T‐DNA integration caused a cascade of new junctions. Several reports have shown that Agrobacterium transformation would delay the closure of DSB (Vaghchhipawala et al ., ; Park et al ., ). We hypothesize that Agrobacterium could hijack the DSB repair mechanism of target cells and provide the opportunity to heterogeneous T‐DNA integration and occurrence of new junctions.…”
Section: Discussionmentioning
confidence: 97%
“…Although the initial steps of the transformation are relatively clear, the final step of how T‐DNA is integrated into the plant genome is not fully understood yet (Tzfira et al ., ; Park et al ., ). In the single‐stranded T‐DNA integration models, including single‐stranded‐gap repair (SSGR) and microhomology‐dependent model, the target site has a single‐stranded gap or bulb (Tinland et al ., ; Tzfira et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…tumefaciens (Friesner and Britt, 2003;Gallego et al, 2003). However, in other studies, contradictory data indicated that Arabidopsis ku80 or ku70 (At1g16970) mutant plants and rice plant lines downregulated in ku70, ku80, or lig4 showed different transformation responses (van Attikum et al, 2001;Friesner and Britt, 2003;Gallego et al, 2003;Li et al, 2005b;Jia et al, 2012;Nishizawa-Yokoi et al, 2012;Vaghchhipawala et al, 2012;Mestiri et al, 2014;Park et al, 2015). These discrepancies might be the result of different techniques and different plant tissues used to examine transformation efficiency, or they may reveal more complex and redundant pathways for T-DNA integration mechanisms during A. tumefaciens infections (Tzfira et al, 2004a;Citovsky et al, 2007;Gelvin, 2010aGelvin, , 2010bMagori and Citovsky, 2012;Lacroix and Citovsky, 2013).…”
Section: Integration Into the Plant Genome And Expression Of The T-dnamentioning
confidence: 99%
“…Integration and/ or expression of T-DNA AtLIG4 (DNA ligase IV) At5g57160 Ziemienowicz et al, 2000;Friesner and Britt, 2003;van Attikum et al, 2003;Zhu et al, 2003a;Nishizawa-Yokoi et al, 2012;Park et al, 2015KU80 At1g48050 van Attikum et al, 2001Friesner and Britt, 2003;Gallego et al, 2003;Li et al, 2005b;Nishizawa-Yokoi et al, 2012;Jia et al, 2012;Mestiri et al, 2014;Park et al, 2015KU70 At1g16970 van Attikum et al, 2001Li et al, 2005b;Nishizawa-Yokoi et al, 2012;Jia et al, 2012;Mestiri et al, 2014;Park et al, 2015 MRE11 (meiotic recombination 11) At5g54260 van Attikum et al, 2001;Jia et al, 2012; XRCC1 (homolog of X-ray repair cross complementing 1) At1g80420 Mestiri et al, 2014;Park et al, 2015 XRCC2 (homolog of X-ray repair cross complementing 2) At5g64520 Mestiri et al, 2014;Park et al, 2015 XRCC4 (homolog of X-ray repair cross complementing 4) At3g23100 Vaghchhipawala et al, 2012;Park et al, 2015 XPF/RAD1/UVH1 (ultraviolet hypersensitive 1) At5g41150 Nam et al, 1998;Mestiri et al, 2014;Park et al, 2015 PARP1 (poly(ADP-ribose) polymerases 1) At2g31320 Jia et al, 2012;Park et al, 2015 HTA1 (histone H2A) At5g54640 Nam et al, 1999;Mysore et al, 2000a, b;Yi et al, 2002Yi et al, , 2006…”
Section: Referencesmentioning
confidence: 99%
“…DAPI (4 0 ,6-diamidino-2-phenylindole) staining of pollen grains was performed as described by Park et al (2015), and viewed on a Zeiss LSM 510 META Axiovert 200M inverted confocal microscope pollen tube germination was performed according to published procedures (Rodriguez-Enriquez et al, 2013).…”
Section: Analysis Of Pollenmentioning
confidence: 99%